RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS PENYEBARAN LOKASI HUTAN LINDUNG PADA PROVINSI LAMPUNG - -, Amnah - (244-5567)
The Geographic Information System was firstly constructed in 1960 which was aimed at solving a geographic problem. It is a computer-based information system which combines mapcomponents (geographic) and map data attribute. One of information systems currently needed is a geographic information system of nature reserve location spread in Lampung province. This system will provide information on locations of natural reserves, natural reserve width, and kindsof flora and fauna. The information that will be presented based on mapping of Lampung province regions is constructed based on coordinate points and area in the form of data. It is a web-based system developed using prototype method which is an object-oriented method. The functional approach described at the system uses UML (Unified Modeling Language).This system can provide information on map description, nature reserve data, and natural reserve locations in Lampung province. The tools used in constructing the geographic information system are ArcView 3.3, PHP, and MySQL. The geographic information system yielded can integrate spatial data and non-spatial data.Keywords: Geographic Information System, Nature Reserves.